Neuropathic Pain as Main Manifestation of POLG-Related Disease: A Case Report - Lang-Orsini, Melanie; Gonzalez-Perez, Paloma (Frontiers in Neurology, 2022)
Mutations in nuclear-encoded genes that are involved in mitochondrial DNA replication and maintenance (e.g., POLG) have been associated with chronic progressive external ophthalmoplegia (CPEO) phenotype. These nuclear genome mutations may lead to multiple mitochondrial DNA deletions or mitochondrial DNA depletion. On the other hand, primary genetic defects of mitochondrial DNA (such as single large-scale deletion or point mutations) have also been associated with the CPEO phenotype. Chronic progressive external ophthalmoplegia (CPEO) may be a manifestation of specific syndromes that, when clinically recognized, prompt clinicians to investigate specific genetic defects. Thus, CPEO, as part of Kearns Sayre syndrome, suggests the presence of a large-scale deletion of mitochondrial DNA. However, in pure CPEO or CPEO plus phenotypes, it is more difficult to know whether causative genetic defects affect the nuclear or mitochondrial DNA. Here, we present a patient with a long-standing history of CPEO plus phenotype, in whom the sequencing of mitochondrial DNA from skeletal muscle was normal, and no other genetic defect was suspected at first. At the time of our evaluation, the presence of polyneuropathy and neuropathic pain prompted us to investigate nuclear genetic defects and, specifically, mutations in the POLG gene. Thus, the sequencing of the POLG gene revealed p.Thr251Ile and p.Pro587Leu mutations in one allele, and p.Ala467Thr mutation in another allele. Although one would expect that mutations in POLG lead to multiple mitochondrial DNA deletions or depletion (loss of copies), the absence of mitochondrial DNA abnormalities in tissue may be explained by heteroplasmy, a lack or no significant involvement of biopsied tissue, or a sampling bias. So, the absence of secondary mitochondrial DNA alterations should not discourage clinicians from further investigating mutations in nuclear-encoded genes. Lastly, mitochondrial point mutations and single mitochondrial DNA deletions very rarely cause CPEO associated with polyneuropathy and neuropathic pain, and POLG-related disease should be considered in this scenario, instead.